Tax Revenue Mobilization Episodes in Emerging Markets and Low-Income Countries : Lessons from a New Dataset - Akitoby, Bernardin (IMF Working Papers; Working Paper ;, 2018)
How do countries mobilize large tax revenue-defined as an average increase in the tax-to-GDP ratio of 0.5 percent per year over three years or more? To answer this question, we build a novel dataset covering 55 episodes of large tax revenue mobilization in low-income countries and emerging markets. We find that: (i) reforms of indirect taxes and exemptions are the most common tax policy measures; (ii) multi-pronged tax administration reforms often go hand in hand with tax policy measures or are stand alone; and (iii) sustainability of the episodes hinges on tax administration reforms in the key compliance areas (risk-based audits, registration, filing, payment, and reporting).